Trabalho intermitente e riscos psicossociais: análise da lei brasileira à luz do direito fundamental ao meio ambiente do trabalho equilibrado - ALMEIDA, Cynthia Campello Rodrigues de (Universidade Federal do Pará, 2021)
This present research aims to identify if the legal regulation of intermittent work introduced into the Brazilian legal order by the Law number 13.467/2017 implies in intolerable psychosocial risks to the workers submitted to this contractual modality. Therefore, it is made an initial overview about the intersection between Environmental Law and Labor Law to define the importance of a balanced work environment as guarantee of mental health protection to the people who are exposed to certain legal and labor contexts. Then, it is analyzed the legal order of intermittent work in foreign experiences, such as Italy, United Kingdom and Portugal, and then compared to the Brazilian legislator choices, to realize what are the motivation to the rule alteration, if there was flexibilization in the labor rights, and if the changes matter in consequences for the balance of the work environment and health of the intermittent workers. Finally, the psychosocial risks involved in the legal regulation of intermittent work are analyzed, what legal treatment is given to these potential attackers of mental health in national legislation, and the implications to the mental health for the intermittent worker. This is a theoretical work, and the hypothetical-deductive approach was used. The research was the descriptive type and was structured through the monographic method, using bibliographic and legislative research, and the data were analyzed by the qualitative content. The achieved results show that the legal order of the intermittent work contract by the Law number 13.467/2017 implies in intolerable psychosocial risks to these workers. As the analysis of Labor Reform shows that the speed in its approval and the lack of discerning studies about the changes to be implemented brought direct repercussion for the balance of the work environment and the workers’ mental health, making it difficult to enforce the fundamental workers’ social rights presents in the Republic Constitution of 1988. Thus, it is concluded that the Brazilian legal order about the intermittent work can bring intolerable psychosocial risks to the workers who are inserted in a working environment ruled by this modality.